Life Satisfaction Among Older Filipino Sexual Minorities and Their Experiences of Support. - Guevara, C. C.
Studies have shown conflicting views on whether or not sexual minorities aged sixty and above face the same challenges of aging that heterosexual persons do. In the Philippines, few studies feature the intersections of age and sexual orientation. This study discusses the perceived life satisfaction of five male and five female sexual minorities between ages sixty to seventy, considering that they have lived in environments of strong heteronormative beliefs reinforced by Filipino family values influenced by the state and cultural/religious institutions. Through interviews with ten older sexual minority respondents, I explore their experiences of acceptance and rejection from their families and friends. I look at how the factors of sexual orientation, gender identity, and expression (SOGIE) may have affected the quality of support they receive as they age, and ultimately, how these influence their disposition as they experience changes brought by aging. Results of this study show the respondents? fears and insecurities over their lack of familial support, which can be attributed to how their sexual and gender identities have been stigmatized.